Reliability of lower-limb strength tests according to maturity status in young male elite football players - Violin, M.; Abaïdia, A. E.; Barthélémy, B.; Ravé, G.; Blazevich, A. J.; Ratel, S. (International Journal of Sports Physiology and Performance, 2026)
Purpose: Lower-limb strength assessment is essential for talent identification, training program design, and return-to-play decisions. However, the influence of biological maturity on test reliability remains unclear, particularly in prepubertal players whose motor coordination is still developing. This study examined the test-retest reliability of dominant-limb abduction, adduction, and anterior and posterior chain tests in elite youth football players, and compared reliability across maturity stages and movement types.